2023
DOI: 10.3390/biology12040532
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Selection Signatures of Domestication in Geese

Abstract: The goose is an economically important poultry species and was one of the first to be domesticated. However, studies on population genetic structures and domestication in goose are very limited. Here, we performed whole genome resequencing of geese from two wild ancestral populations, five Chinese domestic breeds, and four European domestic breeds. We found that Chinese domestic geese except Yili geese originated from a common ancestor and exhibited strong geographical distribution patterns and trait different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…The results of the genetic population analysis showed that there was significant genetic variation among strains. The genetic differentiation of germplasm often exhibits a notable correlation with geographic origins [58][59][60]. Previous studies on wheat germplasm resources, while not differentiating local varieties based on their specific origins, intriguingly classified local varieties from the same area into corresponding groups and clusters, aligning closely with the outcomes of this research [61].…”
Section: Genetic Relationships Among S Rugosoannulata Varietiessupporting
confidence: 75%
“…The results of the genetic population analysis showed that there was significant genetic variation among strains. The genetic differentiation of germplasm often exhibits a notable correlation with geographic origins [58][59][60]. Previous studies on wheat germplasm resources, while not differentiating local varieties based on their specific origins, intriguingly classified local varieties from the same area into corresponding groups and clusters, aligning closely with the outcomes of this research [61].…”
Section: Genetic Relationships Among S Rugosoannulata Varietiessupporting
confidence: 75%
“…China is the world's largest goose-raising country, with production reaching 4.29 million tons in 2021 [2]. Apart from the Ili goose, the origin of Chinese geese can be traced 2 of 16 back to the Swan goose (Anser cygnoides), with 30 different local breeds [3]. Compared with European geese, Chinese geese have more slender necks.…”
Section: Introductionmentioning
confidence: 99%